Phenotype of Idiopathic Epilepsy in Great Swiss Mountain Dogs in Germany—A Retrospective Study - Ostermann, Theresa Elisabeth; Nessler, Jasmin Nicole; Urankar, Hildegard; Bachmann, Norbert; Fechler, Christel; Bathen-Nöthen, Andrea; Tipold, Andrea (Frontiers in Veterinary Science, 2022)
Genetic predisposition of idiopathic epilepsy (IE) has been demonstrated in individual breeds. According to the responsible breeding association in Germany, the average incidence of registered Great Swiss Mountain Dogs (GS) with seizures between the years 1999-2019 is 2.56 %, a genetic predisposition in this breed is suspected. In order to describe the seizure phenotype and to examine seizure causes, a questionnaire-based study was performed. In cooperation with the Swiss Mountain Dog Association of Germany e.V. (SSV e.V.) 114 questionnaires, filled in by owners of GS displaying seizures and filled in by their respective veterinarians between the years 2005 to 2021 were evaluated. Seizure characteristics, clinical and further examinations, treatment, treatment responses and pedigree information were collected. IE was classified according to the International Veterinary Epilepsy Task Force (IVETF) consensus proposal. In the current study 94 (83.06 %) dogs had IE (suspected genetic epilepsy) confirmed with confidence level TIER 1, 2 or 3. The remaining 20 dogs showed signs of structural epilepsy, reactive seizures, or epilepsy of unknown cause and were therefore excluded from further analysis. The average age at seizure onset was 28,83 months. Male GS were significantly more often affected by IE than females. The most common seizure type were focal evolving into generalized seizures (64.5 %). Seizures often began with vomiting, retching or salivation. Cluster seizures (CS) (48.9 %) and status epilepticus (SE) (37.2 %) were observed in a large proportion of dogs. During the observation time a total of 49 animals (52.13 %) died. Out of those 19 dogs (20.21 %) were euthanized in SE or during CS and 14 dogs (14.9 %) died spontaneously during CS or SE. The median age at death was 4 years, and the median survival time for the time, when the dog was suffering from seizures, was found to be 18 months. Both occurrence of CS (p=0.0076) and occurrence of SE (p=0.0859) had an impact on survival time. In GS idiopathic epilepsy presents with a severe phenotype with frequently occurring CS and SE. This study could serve as basis for further genetic evaluations as well as to provide individual treatment recommendations.